Xingnao Jiutan tablets modulate gut microbiota and gut microbiota metabolism to alleviate cerebral ischemia/reperfusion injury - Chen, Yanyan; Zhang, Jing; Hou, Xiaoran; Cai, Shijiao; Zhang, Jingyue; Gou, Yidan; Zhang, Hanxu; Zhai, Yang; Yuan, Hengjie (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionXingnao Jiutan tablets (XNJT), a compound Chinese medicine, have been applied to the treatment of the sequelae of cerebral thrombosis or cerebral hemorrhage, transient cerebral ischemia, and central retinal vein obstruction, etc., but the underlying mechanisms are not yet clear. This research focused on examining the impact of XNJT for cerebral ischemia/reperfusion (MCAO/R) injury, utilizing gut microbiota and metabolomic studies.MethodsThe primary components of XNJT were identified through the application of the HPLC technique. We established a MCAO/ R model in mice and conducted behavioral evaluations, cerebral blood flow measurements, and TTC staining. We used ELISA, high-throughput 16S rDNA gene sequencing, and metabolomics techniques to detect inflammatory factors, microbial populations, and metabolites, respectively. Finally, we performed Spearman correlation analysis to investigate the relationships among gut microbiota and metabolites, comprehensively exploring the mechanisms of XNJT to alleviate cerebral ischemia-reperfusion injury.ResultsWe discovered that XNJT effectively enhanced neurological performance, alleviated cerebral infarction, diminished neuronal cell death, and increased cerebral blood flow. Moreover, XNJT downregulated the secretion of pro-inflammatory cytokines like TNF, IL-6, and IL-1b. Additionally, XNJT improved gut microbiota levels in MCAO/R mice, particularly Bacteroides, Firmicutes, Escherichia-Shigella, and Ligilactobacillus. Furthermore, XNJT primarily modulated differential metabolites in the gut through Glycerophospholipid, Linoleic acid, and Sphingolipid metabolism pathways. Spearman correlation analysis revealed significant associations among intestinal microbiota and various metabolites.DiscussionIn summary, our findings suggest that XNJT can improve cerebral ischemia/reperfusion injury outcomes, reduce inflammatory responses, and regulate gut microbiota and differential metabolites. It’s possible that the potential mechanisms are connected to controlling gut microbiota and metabolism.